Analysis of Emission and Fuel Economy in a Plug in Hybrid Vehicle Using Various Control Strategies - Dr. Karthik M; Nandhakumar T; Dr. Usha S (Journal of Power Electronics and Devices, 2016)
Plug-in hybrid electric vehicles (PHEVs) differ from hybrid vehicles (HEVs) with their capability to use off-board electricity generation to recharge their battery. Electric vehicles are highly emerging for transportation purpose, which have been developed over the past several decades due to various environmental concerns. Pure electric vehicles currently do not have adequate range when powered by batteries alone and also recharging of it requires several hours. The shortcoming raised with the standalone energy source powered electric vehicle made to think about an alternative option for an electric vehicle and motivated towards the hybridization of energy sources in electric vehicle. This paper analyzes the equivalent power circuit and operation principles of a PHEV using UDDS and NEDC driving pattern. Regenerative braking also provides an effective way of extending the driving range of battery powered electric vehicles. Conventional automobiles use Internal Combustion Engines (ICEs) to operate with the energy source from fossil fuels. However, the conventional vehicle system provides limited fuel economy, as well as producing harmful air pollutants. A Plug-in Hybrid Electric Vehicle (PHEV) has been introduced which operates within its all electric range. Which have high capacity of energy storage system. PHEVs used to charge the battery from electricity grid, which differs from the traditional Hybrid Electric Vehicles (HEVs). The plug in hybrid electric vehicle is instigated for enhancing the vehicle performance by improving the fuel economy, effectively capturing the regenerative braking energy by controlling the Battery State of Charge (SoC) level within the optimal upper and lower bound that would improve the battery life, eliminating the fuel starvation problem and maximizing the drivability of the vehicle through an optimized distribution of the required power to the load. The proposed work is focused on designing a gasoline based Hybrid Electric Vehicle includes the modelling of hybrid energy sources and other interfacing structures.